Design and Build a Child's Learning Room Application, in Increasing Learning Motivation Based on Android - Antonius Yadi Kuntoro; Hermanto Hermanto (Jurnal Mantik, 2020)
Millennials are often associated with the term “kids zaman now” or "children of today." If we associate today's children with previous habits, then we will find different things there. It affects their motivation to study at school. While teaching in schools still uses a conventional model, better known as Teacher-Centered Learning (TCL), the model is boring for today's students. As a result, many students today find it challenging to understand the lessons learned at school, and arriving at their homes is again preoccupied with their gadgets and forgetting the subject matter learned in school. Children's Learning Room application ranging from early childhood to elementary and junior high school students can provide a pleasant atmosphere in the child's learning process; besides, this App can be played without any difficulty by the child in its use. At the app creation stage, there are three stages of testing: functional testing, device testing, and user interest testing. From due diligence using questionnaires from 30 respondents from three professions, namely students, teachers, and parents of students with 12 questions asked on the questionnaire, most respondents agreed, or positive responses got 95.4% of the responses strongly agreed. It can be said that this Children's Learning Room Application is suitable for early childhood to elementary school children computer technology.